The Visual Impact of Colors in Ottoman Inscriptions: A Case Study of the Sultan Bayezid II Mosque in Didymóteichon, Greece - Ameen, Ahmed; Kasem, Yassmin Youssef (Journal of Islamic Architecture, 2025)
This study undertakes a comprehensive examination of color as a distinctive and impactful feature in the artistic and architectural expressions of the Ottoman Empire, with a specific focus on its visual impact on historical inscriptions in Greece. By delving into the reasons and motivations underlying the Ottomans' extensive use of color, this research elucidates the effect it had on the viewer's perception and interpretation. Applying this analytical lens to the oldest extant Ottoman Mosque in Greece, the Sultan Bayezid II Mosque in Didymóteichon, the paper presents a nuanced exploration of the visual impact generated by color within the inscriptional elements of this significant edifice. The findings demonstrate how the Ottomans' strategic deployment of color, mainly through the skilful juxtaposition of contrasting hues and harmonious combinations, enhances the aesthetic appeal of the inscriptions, conveying a tangible sense of authority and captivating the viewer's attention. This research provides a novel perspective for understanding the sophisticated visual communication strategies employed in Ottoman epigraphy, underscoring the pivotal role of color as a crucial element in shaping the inscriptions' visual resonance and symbolic import. This study offers valuable insights into the cultural, aesthetic, and communicative dimensions of Ottoman visual culture by illuminating the multifaceted significance of chromatic expression within this artistic tradition.